2023
DOI: 10.3390/jfb14020112
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Spectral Characterisation of Fabricated Cerium-Doped Magnesium Oxide Nanoparticles: Evaluation of the Antimicrobial Potential and Its Membranolytic Activity through Large Unilamellar Vesicles

Abstract: Considerable attention has been given to Magnesium oxide nanoparticles lately due to their antimicrobial potential, low toxicity to humans, high thermal stability, biocompatibility, and low cost of production. However, their successful transformation into sustainable drugs is limited due to their low membrane permeability, which reduces their bioavailability in target cells. Herein we propose Cerium-doped magnesium oxide nanoparticles (MgOCeNPs) as a powerful solution to above mentioned limitations and are com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…This result agrees with [20] when they exposed that magnesium oxide NPs were effective antibacterial against P. aeruginosa so that inhibition zone gradually increases with increasing concentrations of imported magnesium oxide nanoparticles.…”
Section: Imported Magnesium Oxide Nanoparticlessupporting
confidence: 88%
“…This result agrees with [20] when they exposed that magnesium oxide NPs were effective antibacterial against P. aeruginosa so that inhibition zone gradually increases with increasing concentrations of imported magnesium oxide nanoparticles.…”
Section: Imported Magnesium Oxide Nanoparticlessupporting
confidence: 88%
“…Additionally, the proposed bionanocomposite exhibited higher antifungal activity as compared to pure magnesium oxide and cellulose, respectively. Khatua and co-researchers [165] prepared pure magnesium oxide and cerium-doped magnesium oxide nanoparticles through a facile and low-cost wet chemical approach. They reported that cerium-doped magnesium oxide nanoparticles presented increased fungicidal activity and cytotoxicity against plant pathogenic fungi (THY-1) compared to pure magnesium oxide nanoparticles.…”
Section: Antifungal Activitymentioning
confidence: 99%
“…Recently, mechanical milling has emerged as an effective method for the synthesis of copper oxide and tin oxide nanoparticles due to its simplicity, scalability, and costeffectiveness [10]- [13]. Mechanical milling involves the grinding of bulk materials in the presence of a reducing agent to produce nanoparticles.…”
Section: Introductionmentioning
confidence: 99%